Spectral Results of Sturm-Liouville Difference Equation with Dirichlet Boundary Conditions - Bas, Erdal; Ozarslan, Ramazan (Amer Inst Physics, 2016)
In this work, the boundary value problem for Sturm-Liouville difference equation, which has variable potential function q(n), with Dirichlet boundary conditions is considered. The sum representation of solution is obtained and by virtue of this result, asymptotic formula of the eigenfunction is given.
International Conference on Advances in Natural and Applied Sciences (ICANAS) -- APR 21-23, 2016 -- Antalya, TURKEY
Keywords: Eigenvalues